A Cross-Sectional Study on Behavioral Manifestation in Alzheimer’s Disease Patients and their Association with Cognitive Impairment - Rizwan Farooq, Unaiza Jawad, Imran Khan, Muhammad Rehman, Muhammad Shoaib Irfan, Subhan Ullah, (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Dementia psychological and behavioral symptoms are significantly associated to Alzheimer’s disease (AD). Clinical profile and characterization of Alzheimer’s disease patients might assist in evolution, diagnosis, and better treatment of the disease. The present study aimed to evaluate the behavioral manifestation of Alzheimer’s disease patients. Methodology: This multi-centered cross-sectional study was carried out on 96 Alzheimer’s disease patients in the department of Psychiatry Lahore General Hospital and Psychiatry unit, Khyber Teaching Hospital Peshawar, Pakistan for duration of six months from 1st July 2021 to 30th December 2021. Alzheimer’s disease patients with lower and higher Behavioural and psychological symptoms of dementia (BPSD) scores (≤25 and 26-50 respectively) were enrolled. The patient’s demographic details and clinical information were gathered. Mini-Mental State Examination (MMSE) was used for the evaluation of dementia severity whereas severity varies from mild 27-21 to severe ≤10. Demographic details, AD pharmacological treatments, psychotic breaks presence, AD diagnosis, treatment of concomitant diseases, and extrapyramidal symptoms such as hypokinesia, fluctuating cognition, tremors, etc. were secondary outcomes. Results: Of the total 96 AD patients, 44 (45.8%) had higher and 52 (54.2%) had lower BPSD scores. About 62 (64.6%) were women and 34 (35.4%) were male patients. The overall mean age was 79.6±8.4 years. The majority of the patients had a BPSD score at inclusion and the incidence of psychotic out breaks was reported in 19 (19.8%) patients. The prevalence of symptoms such as depression, delusions, lack of concentration, lack of cooperation, and tremors was 41 (42.5%), 33 (34%), 52 (54.6%), 34 (35.9%), and 52 (54.6%) respectively. Psychotic symptoms such as hallucinations, delusions, and delirium were significantly prevalent in patients with high BPSD scores whereas Apathy and tearfulness-like emotional symptoms were predominated in lower BPSD patients. ADAS-non cognitive score and MMSE were adversely related (p=0.0314), signifying BPSD and cognitive impairment correlation. Appetite changes and lack of concentration were prominently associated with MMSE (p=0.035 and 0.052). Conclusion: Our study found a higher prevalence of non-cognitive symptoms in Alzheimer’s disease patients. Also, BPSD and cognitive impairment are significantly associated with AD. ADAS-non cognitive is a useful assessment tool.